Amyloid precursor protein and C99 are subunits in human microglial Hv1 channels that enhance current and inflammatory mediator release - Ruiming Zhao; Punyanuch Sophanpanichkul; Jean Paul Chadarevian; Yiwen Ding; Hui Dai; Maha Nayak; Hayk Davtyan; Mathew Blurton-Jones; Steve A. N. Goldstein (Proceedings of the National Academy of Sciences, 2025)
In Alzheimer’s disease (AD), hyperactivated microglia produce inflammatory mediators that contribute to neuroinflammation and neuronal damage. Amyloid precursor protein (APP), a transmembrane protein expressed in many cell types, including neurons and microglia, plays a critical role in AD pathogenesis via its secretase-mediated processing to release the C-terminal 99-residue transmembrane fragment (C99) that is further cleaved to yield amyloid-β peptides. Voltage-gated proton channels (Hv1) have been implicated in microglial activation and release of inflammatory mediators, but the potential role of these channels in human microglia and AD pathogenesis remains unclear. Here, we demonstrate that human induced pluripotent stem cell–derived microglia (iMG) express native Hv1 channels with biophysical and pharmacological attributes determined by their coassembly with APP and that APP knockdown decreases Hv1 currents, suppressing cytokine and reactive oxygen species release. In HEK293T cells, APP is shown to increase current by favoring channel opening at more negative membrane potentials. C99 is sufficient to assemble with Hv1 and alters channel function even more significantly than APP. Coimmunoprecipitation, total internal reflection fluorescence microscopy, and altered pharmacology further demonstrate that C99 forms stable complexes with Hv1 in the plasma membrane. In addition, we find that two early-onset AD mutations in APP (E682K and D694N) that reside within C99 significantly increase voltage-dependent channel activity beyond that induced by wild type C99, rationalizing their enhanced mediation of neuroinflammation.